Parvalbumin Interneurons Determine Emotional Valence Through Modulating Accumbal Output Pathways - Chen, Xi; Liu, Zhiyuan; Ma, Chaonan; Ma, Lan; Liu, Xing (Frontiers in Behavioral Neuroscience, 2019)
Parvalbumin (PV) expressing GABAergic interneurons provide large source of GABA to spiny projection neurons (SPNs) in the striatum. However, the roles of PV+ interneurons in regulation of SPNs in the ventral striatum and emotional states are largely unknown. Here we investigated whether stimulation of ventral striatal (accumbal) PV+ interneurons will drive emotional valence in mice. We found that during conditioned place preference (CPP) training, activation of accumbal PV+ interneurons evoked place preference, while suppressing them resulted in conditioned place aversion (CPA). Activation of PV+ interneurons during place conditioning increased c-fos expression in SPNs in the direct pathway (dSPNs) and impaired lithium chloride-induced CPA. Activation of dSPNs and SPNs in the indirect pathway (iSPNs) induced CPP and CPA, respectively; conversely, suppression of dSPNs or iSPNs induced CPA or CPP. In addition, activation or suppression of calretinin-expressing (CR) GABAergic interneurons did not induce place preference. These data suggest that PV+ interneurons can bidirectionally determine the emotional valence through their regulation of accumbal SPN activities and raise the possibility that manipulation of PV+ interneuron activity may have the potential to alter behavioral consequences in response to psychostimulants.